AMPA receptors in the evolving synapse: structure, function, and disease implications - Francis, Fleming; Chettri, Dewan; Nair, Deepak (Frontiers in Synaptic Neuroscience, 2025)
Synapses, once considered static conduits for neuronal signals, are now recognized as dynamic, multifunctional structures critical to brain function, plasticity, and disease. This evolving understanding has highlighted the tripartite nature of synapses, including pre-synaptic terminals, post-synaptic compartments, and regulatory glial elements. Among excitatory synapses, glutamatergic transmission dominates, with AMPA receptors (AMPARs) playing a central role in fast synaptic signaling. AMPARs are tetrameric, ligand-gated ion channels that mediate rapid depolarization and are tightly regulated by subunit composition, trafficking, and interactions with scaffolding and signaling proteins. Their activity-dependent modulation underpins key processes such as long-term potentiation and depression, central to learning and memory. Importantly, dysfunctions in AMPAR expression, localization, or signaling are increasingly linked to neurological and psychiatric disorders including autism spectrum disorders, epilepsy, schizophrenia, and Alzheimer's disease. This review discusses AMPAR biology in the context of synaptic organization, highlighting recent advances and ongoing challenges in understanding their roles in health and disease.